Transvaginal Ultrasound and Doppler Features of Intraligamental Myomas. (16th January 2020) - Ambrosio, Marco; Raimondo, Diego; Savelli, Luca; Salucci, Paolo; Arena, Alessandro; Borghese, Giulia; Mattioli, Giulia; Giaquinto, Ilaria; Scifo, Maria Cristina; Meriggiola, Maria Cristina; Casadio, Paolo; Seracchioli, Renato
Abstract : Objectives: To describe the ultrasound (US) features of intraligamental myomas (IMs) using Morphological Uterus Sonographic Assessment group standardized terminology. Methods: This was a retrospective monocentric study. A total of 125 consecutive women with a preoperative US diagnosis of a myoma located close to the uterine isthmus (International Federation of Gynecology and Obstetrics stages 5, 6, and 7) from 2016 to 2019 who underwent laparoscopic or laparotomic myomectomy or hysterectomy were included for study analyses. The US data were retrieved from US reports and stored digital images by 2 authors. Ultrasound features of myomas were described according to Morphological Uterus Sonographic Assessment terminology. Clinical data for the study population were retrieved from the patients' records. Results: Nineteen women with a surgical confirmation of an IM were included in the study group; the remaining population constituted the control group (n = 106). Non‐uniform echogenicity was detected in 17 of 19 (89%) of IMs compared to 26 of 106 (25%) fibroids in the control group ( P  < .001). The presence of shadowing was detected in 12 of 19 (63%) IMs compared to 94 of 106 (89%) cases in the control group ( P = .004). Intraligamental myomas were more vascularized tumors compared to myomas in the control group ( P = .004). Transvaginal US showed high specificity for the diagnosis of an IM (0.93; 95% confidence interval, 0.87–0.96). Conclusions: On US imaging, IMs appear as vascularized solid tumors with nonuniform echogenicity; cones of shadows were less frequent in IMs than the control group, and this finding can help in the differential diagnosis. Knowledge of their specific US features could help sonographers make an accurate diagnosis, allowing them to plan correct surgery and avoid severe complications.